A Program for Stochastic Simulation of Econometric Models - Bianchi, Carlo; Calzolari, Giorgio; Corsi, Paolo (Econometrica, 1978)
model. Many results (observed value, deterministic solution, computed mean among the replications, minimum and maximum of the stochastic solution, first relative differences of the observed, deterministic and mean stochastic values) are displayed and several empirical indicators of goodness of fit are computed: (1) the mean over the simulation period of the actual, deterministic and mean stochastic values; (2) the root mean square error (RMSE) of the deterministic and mean stochastic solutions; (3) the mean absolute percentage error (MAPE) of the deterministic and mean stochastic solutions; (4) Theil's inequality coefficient (U) of the deterministic and mean stochastic solutions; (5) the coefficients and standard errors of the regression (with intercept) of the observed values on the deterministic or mean stochastic solutions; (6) the coefficients and standard errors of the regression (without intercept) of the first relative differences of the observed values over those of the deterministic or mean stochastic solutions. The package is written in FORTRAN IV and ASSEMBLER 370 languages. It consists of approximately one thousand statements, in addition to the statements necessary to formalize the model. The required storage for the program is 60 kilobytes. A large work matrix is then required to hold intermediate and final results of the computation; its dimensions depend on the parameters specified in the input file (number of equations, simulation period, number of variables, etc.). The stochastic simulation of the Klein I model requires about 13 seconds of CPU time for 100 replications over 21 years of the sample period.